Reference values of IGF1, IGFBP3 and IGF1/IGFBP3 ratio in adult population in the Czech Republic - Kucera, Radek; Topolcan, Ondrej; Pecen, Ladislav; Kinkorová, Judita; Svobodova, Sarka; Windrichová, Jindra; Fuchsova, Radka (Clinica chimica acta, 2015)
BACKGROUND: IGF1 is responsible for regulation of growth, metabolism and differentiation of human cells. IGFBP3 is the most abundant of the carrier proteins for IGF1 in the blood. IGF1/IGFBP3 molar ratio is an indicator of IGF1 bioavailability. We decided to create a file of reference ranges of IGF1, IGFBP3 and IGF1/IGFBPP3 ratio for the adult Czech population across the age spectrum. METHODS: We selected a group of 1022 subjects, 467 males and 555 females (ages 20-98 years), from several regions in the Czech Republic. The group consisted of blood donors and patients undergoing regular preventive examinations. Serum levels of IGF1 and IGFBP3 were measured using the following radioimmunoassay kits: IRMA IGF1 (Immunotech, Marseille, France) and IRMA IGFBP3 (Immunotech, Prague, Czech Republic). The IGF1/IGFBP3 ratio was also calculated. The following groups of patients were excluded: patients with diabetes, high blood glucose, high insulin levels, post-surgery patients, polymorbid patients, and subjects with oncological diseases. Subjects were divided into seven age-groups. Changes in the levels of observed analytes in each decade across the age spectrum were evaluated. All statistical analyses were performed by SAS 9.3 (Statistical Analysis Software release 9.3; SAS Institute Inc., Cary, NC, USA). RESULTS: All three parameters IGF1, IGFBP3 and IGF1/IGFBP3 decreased in parallel with decrease in age: p<0.0001, r=-0.64, -0.35 and -0.54, respectively. The dynamics of the decline was different between males and females. Linear regression models with age as independent variable fitted by gender are displayed in Fig. 1. Non-parametric reference interval curves (medians and 2.5th-97.5th percentiles) for IGF1, IGFBP3 and IGF1/IGFBP3 ratio as function of age by gender are displayed in Fig. 2(a,b,c). All medians and 2.5th-97.5th percentiles were plotted by cubic spline. For males, linear regression models were as follows: IGF1=291.34619-2.41211 × age, IGFBP3=2931.62778-6.11659 × age, IGF1/IGFBP3=0.02897-0.00021213 × age. For females, we plotted the following: IGF1=241.67406-1.98466 × age, IGFBP3=3688.60561-16.39560 × age, IGF1/IGFBP3=0.02029-0.00013233 × age. IGF1 was statistically significantly higher in males with p<0.0001 (Wilcoxon test) but decreased faster (p=0.0121). IGFBP3 was statistically significantly higher in females with p=0.0004 (Wilcoxon test) but decreased faster (p<0.0001). IGF1/IGFBP3 was statistically significantly higher in males with p<0.0001 (Wilcoxon test) but decreased faster (p<0.0001). CONCLUSION: Authors recommend using of a linear regression model based reference ranges for IGF1, IGFBP3 and IGF1/IGFBP3 ratio and using different reference ranges for genders.
Keywords: dospělí; Insulin-Like Growth Factor I; Female; IGFBP-3; Adult; Linear Models; mladý dospělý; ženské pohlaví; Aging; lidé; Radioimmunoassay; Aged, 80 and over; lineární modely; referenční hodnoty; Sex Characteristics; Insulin-Like Growth Factor Binding Protein 3; insulinu podobný růstový faktor I; Male; Aged; Czech Republic; Reference Values; Young Adult; pohlavní dimorfismus; stárnutí; Česká republika; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; radioimunoanalýza; Middle Aged; Humans